SOCIAL SECURITY CRISIS-MONGERING: SPORTS FINAL, C Edition - Theodore R Marmor and Fay Lomax Cook Theodore R Marmor is professor of public policy and management at Yale University and Fay Lomax Cook is associate professor of education and social policy at Northwestern University's Center for Urban Affairs and (Chicago tribune (1963), 1988)
Public discussion of Social Security in recent months pointedly illustrates an unsettling pattern in the discourse about social welfare policy-the tendency to jump to crisis rhetoric. To judge from media coverage, Social Security once again is in a state of crisis. The cause of panicky concern is a growing surplus in the program's trust funds: $37 billion in fiscal 1988, and estimated by the Office of Management and Budget to increase to $93 billion by 1993. For most of the 1970s and early '80s, newspaper readers and television audiences were reminded continually that the program's trust funds were close to or literally in "bankruptcy." However, almost all experts now agree that the 1983 legislative changes eliminated the problems that generated the crisis rhetoric then. The 1983 Social Security amendments balanced the books for the short run and, through tax increases and benefit reductions, set in motion a surplus which would grow to substantial amounts-perhaps half a trillion dollars by the year 2015. These surpluses were to finance the substantial anticipated increase in retirees in the third decade of the 21st Century and beyond. In fact, the Social Security surplus is a form of increased national savings which should be gratifying to most economists who bemoan the fact that the United States' rate of savings is one of the lowest in the world. Can it really be that amid worries over the size of the deficit we should be desperately worried about a growing surplus in one part of the government's current accounts? The surplus certainly raises issues for fiscal policy-the degree of stimulus or restraint necessary for economic stability-but it hardly constitutes a desperate problem. If there is a crisis, it is one of political discourse represented by the inability to interpret any news about Social Security as favorable despite the fiscal facts and the rock-solid public support for the program.